GIS-, geochemistry-, and geophysics-based identification of geothermal energy resources in sedimentary basins: a case study of Zindapir Anticlinorium Zone, Eastern Sulaiman Fold and Thrust Belt, Pakistan - Rasheed, Aqeel; Wahid, Ali; Tariq Janjuhah, Hammad; Hameed, Fahad; Ali, Syed Haroon; Talha Riaz, Malik; Kontakiotis, George; Antonarakou, Assimina; Besiou, Evangelia; Shafique, Munib Ahmed (Frontiers in Earth Science, 2026)
Globally, fold and thrust belts are considered promising zones for geothermal energy exploration due to their complex structural geometries. These zones provide favorable conditions that contribute to the trapping and circulation of geothermal resources. However, their inherent structural complexity poses significant challenges in delineating geothermal reservoirs. This study analyzes the geothermal reservoir potential of the Zindapir Anticlinorium Zone, which is part of the Eastern Sulaiman Fold and Thrust Belt in Pakistan. The objectives of this research were achieved by utilizing an integrated approach that involved remote sensing and geochemical, gravity, magnetic, seismic, and petrophysical analyses. The remote sensing data indicated that regional and local tectonic activity, along with the uplift of Eocene and Paleocene rocks, play a significant role in the development of geothermal reservoirs. Additionally, higher land-surface temperature anomalies, active seismicity, and high-gradient streams passing through hot springs are key indicators of geothermal resource potential. The higher ionic concentration of Na+ in the geochemical analysis indicates a deep circulation of water that affects thermal activities. Temperature estimates suggest that the Gulki hot spring lies in a zone characterized by immature thermal water, whereas the hot springs of Jaffarabad and Zindapir originate from subsurface zones with partially equilibrated water. Interpretations of gravity and magnetic data suggest that the anticlines of the Zindapir Anticlinorium Zone have less sedimentary thickness and favorable heat flow conditions. Moreover, seismic and petrophysical analyses indicate that the selected reservoir formations (Pab Sandstone, Lower Goru Formation, and Chiltan Limestone) have the potential to act as geothermal reservoirs. The comprehensive evaluation index (CEI), which incorporates temperature, porosity, and permeability parameters, suggests that the Dhodak, Affiband, Rodho, and Zindapir anticlines are ideal locations for the extraction of economical geothermal reservoirs in the Zindapir Anticlinorium Zone. These anticlines have less sedimentary thickness and compressional tectonic deformation, which allow the up transfer of heat from deeper sources. It is suggested that the workflow of this integrated approach can be implemented in any sedimentary basin to identify potential economic locations of geothermal reservoirs.